Penerapan Manajemen pada Pengelolaan Limbah Medis Padat di Rumah Sakit Tingkat III Brawijaya Surabaya Tahun 2024 - Triyuslina, Cintia; Suryono, Hadi; Narwati; Thohari, Imam (Jurnal Sains, Teknologi dan Kesehatan, 2024)
At the Brawijaya Level III Hospital Surabaya, problems were found in the implementation of solid medical waste management, namely the sorting of medical and domestic waste that was not yet comprehensive, staff who were not compliant with using PPE, and the hemodialysis room that would be made functional. The aim of this research is to evaluate the application of management in solid medical waste management based on management functions (Planning,Organizing,Actuating,Controlling) and utilization of management elements (Man,Money,Material,Machine,Method). This research is a qualitative descriptive research approach cross sectional. The object of this research is solid medical waste management. The subjects of this research were 4 officers cleaning service, environmental health section, PPI committee, and Binayanmasum. Data was collected through interviews and observations. Data analysis was carried out descriptively by describing management functions and management elements. Based on the research results, it is known that the application of management in solid medical waste management obtained a total percentage of 80.7%(good). At the reduction stage it got 44.4%(fair),the sorting stage 88.9%(good),the container stage 95.2%(good),the storage stage 75%(good),the transportation stage 87.5%(good),and the processing 93.3%(good). The implementation of management in the management of solid medical waste at the Level III Brawijaya Hospital Surabaya received the "good" category, with several aspects that had not been fulfilled. Suggestions that can be given are to create a schedule for monitoring officers in complying with SOPs and wearing PPE according to regulations, as well as providing education by placing stickers with images of medical and non-medical waste on rubbish bins.